An analysis of the writing capacity of the students in Hortatory Exposure Text at First semester of the year English Study Program of the Counseling and Education Faculty - Edi Suwandi; Ahmad Tauchid (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The aim of this research is to: 1) The students' ability to write text in hortatory exposures in the first semester of Nadhlatul Ulama Sunan Giri Bojonegoro English program; 2) the difficulties that students experience with the writing of hortatory exposure texts in the first half of Nadhlatul Ulama Sunan Giri Bojonegoro University's English program. This is a mixed form of analysis, which incorporates qualitative and quantitative research. The research participants are 22 representatives from Nadhlatul Ulama Sunan Giri Bojonegoro University's first semester program in English. The data were collected through testing and observation. toryTest has been done to assess students' ability to write the hortatory exposure text and the difficulties encountered by students' ability to write the hortatory exposure text in the first semester of the program of the Nadhlatul Ulama Sunan Giri Bojonegoro University and to recognize all student behaviors or behaviours in writing hortatory exposure. Students had difficulties in the content around 48.70%, in the organization 40.13%, in vocabulary of 38.57%, in grammar around 34.29% and mechanics around 22.85%. This means that students must learn more about the text on hortatory exposure.